Large-amplitude vibrations of thin-walled rotating laminated composite cylindrical shell with arbitrary boundary conditions. (November 2020) - Li, Chaofeng; Li, Peiyong; Zhong, Bingfu; Miao, Xueyang
Abstract: The study of the large-amplitude vibrations of thin-walled rotating laminated composite cylindrical shell with arbitrary boundary conditions is presented in this paper, in which the artificial spring is used to simulate the arbitrary boundary conditions. The nonlinearity is introduced by using Donnell's nonlinear shell theory, and the orthogonal polynomials are used as the admissible displacement functions. By using the Lagrange equation based on the energy method, the governing equation of motion is obtained. Then, the Incremental Harmonic Balance Method (IHBM) and the arc-length method are used in the process of solving the governing equation. The influences of rotating speed, boundary spring stiffness, and geometric parameters on the nonlinear vibration characteristics of the shell are investigated. The results show that these parameters have a significant impact on the nonlinear vibration of the rotating laminated cylindrical shell. Highlights: A dynamic model is established to analyze the thin-wall rotating laminated shells with arbitrary boundary conditions. The large amplitude vibration of rotating shells with geometric nonlinearity is considered. The rotate speed, spring stiffness and structure parameter to geometric nonlinearity must be considered.